IDENTIFIKASI TERJADINYA TRANSFER GEN PADA TANAMAN - Tjokrokusumo, Donowati S (Jurnal Sains dan Teknologi Indonesia, 2010)
Identification of somatic hybridization is one of the important steps to cope with that fusion and migration of gene to be analyzed. Therefore, following fusion various approaches have been used to identify hybrid materials. Putative somatic hybridsmay be confirmed and characterized in a number of ways, depending upon the characteristics of the parental materials. Both characterization and identification methods are discussed in this paper.